The evolution of phyics : - Einstein, Albert (Cambridge University Press, 1978)
Contents: The evolution of phyics is a science book for the lay reader, by Albert Einstein and Leopold Infeld, tracing the development of ideas in physics. It was a popular success, and was featured in a Time magazine cover story.